EPISTEMOLOGI PENDIDIKAN ISLAM NUSANTARA (Studi Interpretatif-Simbolik atas Peran Kampus, Pesantren dan Lembaga Adat) - Hamsyah, Junaidi (Analisis: Jurnal Studi Keislaman, 2015)
THE EPISTIMOLOGY OF ARCHIPELAGO ISLAMIC EDUCATION   (The  interpretative  Study   –  Symbolic  on  the Campus Role, Al-Quran Islamic School and Custom Institution): The Islamic educational institutions need to be back and know the historical  root to confirm the identity,  character, distinctiveness and uniqueness. There is the timeless spirit to underlying model of ideal education in the contemporary era. The history of Islamiceducation  was initiated  by the  trustees  is a reflection  of how Islam should be delivered. In the contemporary era of Indonesian Muslims, the spirit of Islamic education in the style of the trustees found that the momentum and the three existing educational institution are including schools, colleges, and traditional institutions. Those three institutions need the contextual  efforts, synergies,  and  modifications   to  improve.  If  those systems  in the three institutions have been connected,  the epistemology  of Islamic education Archipelago can be realized.